Pemecahan Problem Efisiensi Faktor Produksi dengan Metode Linear Programming - Surahman Surahman (Caraka Tani: Journal of Sustainable Agriculture, 2005)
The problem solving of the production element efficiency by using linear programming can be done by formulating the mathematical model. The principles that have to be kept first are:The whole set of the problems can be divided into activity parts.Each of the activities must have been determined precisely (about the quantity)The quantity must have devided preciselyThe limit of the capacity should be determinedMaking the modelAfter that, the next step is finding the solution. However, one thing to remember is that the problem solving using linear programming is only a medium. About the application depends on the decision maker or the user that will not be out from the real condition.